2019
DOI: 10.1002/rrq.287
|View full text |Cite
|
Sign up to set email alerts
|

The Simple View of Reading Made Complex by Morphological Decoding Fluency in Bilingual Fourth‐Grade Readers of English

Abstract: The authors examined the complexity of the simple view of reading, focusing on morphological decoding fluency in fourth‐grade readers of English in Singapore. The participants were three groups of students who all learned to become bilingual and biliterate in the English language (EL) and their respective ethnic language in school but differed in the home language they used. The first group was ethnic Chinese students who used English as the dominant home language (Chinese EL1); the other two groups were ethni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…Morphological awareness has been the subject of a great deal of research in recent decades. Morphological awareness has been shown to exert a direct influence on reading ability (e.g., Gottardo, Mirza, Koh, Ferreira, & Javier, 2018; Kirby et al, 2012; Zhang & Ke, 2020), is implicated in reading difficulties (e.g., Tong, Deacon, Kirby, Cain, & Parrila, 2011), and is widely understood to be related to both word recognition and language comprehension. Importantly, morphological awareness provides a clear counter to the notion that we can develop reading simply by working on word recognition and oral language, as morphological awareness has a particular value in written text.…”
Section: Word Recognition and Language Comprehension Are Not Entirely Separate And Important Processes Bridge Themmentioning
confidence: 99%
“…Morphological awareness has been the subject of a great deal of research in recent decades. Morphological awareness has been shown to exert a direct influence on reading ability (e.g., Gottardo, Mirza, Koh, Ferreira, & Javier, 2018; Kirby et al, 2012; Zhang & Ke, 2020), is implicated in reading difficulties (e.g., Tong, Deacon, Kirby, Cain, & Parrila, 2011), and is widely understood to be related to both word recognition and language comprehension. Importantly, morphological awareness provides a clear counter to the notion that we can develop reading simply by working on word recognition and oral language, as morphological awareness has a particular value in written text.…”
Section: Word Recognition and Language Comprehension Are Not Entirely Separate And Important Processes Bridge Themmentioning
confidence: 99%
“…Such efforts would contribute to the ongoing efforts by applied linguists and L2 reading scholars investigating how related, but distinct subskills (e.g., vocabulary size vs. depth; vocabulary vs. grammatical knowledge) relatively predict L2 text comprehension. As well, this approach may generate more nuanced insights into reading processes of different groups of readers to provide valuable instructional implications for linguistically responsive pedagogy (see Zhang & Ke, 2020). Additionally, future research needs to examine factors contributing to morphosyntactic awareness development to support students learning complex science vocabulary and engaging with the linguistically complex science texts.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, researchers have historically treated ELs as a monolithic group combining current and former ELs—also referred to as emergent and proficient English speakers—under the same category (see Lawrence, Capotosto, Branum‐Martin, White, & Snow, 2012). This is problematic as evidence suggests that emergent or less proficient speakers of the language may not only have different achievement profiles but may also have different learning needs and may rely on different factors contributing to their success (e.g., Ardasheva et al., 2019; Dockrell, Braisby, & Best, 2007; Lawrence et al., 2012; Van Orman et al., 2021; Zhang & Ke, 2020).…”
mentioning
confidence: 99%
“…Ramirez et al (2011), likewise, found Spanish-speaking ELs, as did monolingual readers, outperformed their Chinese-speaking peers on derivational awareness. In D. Zhang and Ke (2020), morphological decoding fluency significantly predicted reading comprehension for Malay (an Austronesian language with rich and complex derivation)-speaking bilingual readers of English, as opposed to their Chinese-speaking peers. Taken together, the findings of these studies suggested that readers whose L1 is characterized by a productive derivational process like in English showed a processing or developmental advantage, compared to their Chinese-speaking counterpart (henceforth a linguistic distance effect on L2 morphology; see Clahsen et al, 2010).…”
Section: Cross-linguistic Transfer Linguistic Distance and Related Im...mentioning
confidence: 99%
“…As Verhoeven and Perfetti (2011) argued, "reading more complex words may involve processes of morphological decomposition as well as grapheme-phoneme connections and whole-word look-up methods" (p. 458). Inasmuch as word reading (fluency), including morphological decoding fluency, serves as a fundamental basis of text reading and comprehension (Perfetti & Stafura, 2014;Silverman et al, 2013;D. Zhang & Ke, 2020), MA can perhaps be understood to contribute to reading comprehension indirectly through the mediation of word reading (Deacon et al, 2014;Levesque et al, 2017Levesque et al, , 2021Nagy, 2007;J.…”
Section: Binder Of Representations Of Lexical Constituents Redundancy...mentioning
confidence: 99%